Antiviral resistance: influenza B - Conde, Patrícia (2013)
Currently circulating influenza viruses are resistant to adamantanes and except for a low number of sporadic cases most are sensitive to neuraminidase inhibitors (NI). Adamantanes are ineffective against influenza B viruses and although NI-resistant influenza B viruses have been rarely reported, recently in the United States was identified one cluster of influenza B viruses with reduced susceptibility to NI and with the I221V substitution in the active site of the neuraminidase. Despite the low prevalence of oseltamivir-resistant influenza viruses, the constant evolution of influenza requires the monitoring of antiviral resistance among these viruses in the community. This is very important for the clinical management of severe influenza cases as to the detection of novel genetic markers associated with antiviral resistance. This study reports the antiviral susceptibility to neuraminidase inhibitors of influenza B viruses isolated in Portugal during the 2010/2011, 2011/2011 and 2012/2013 seasons. Over the period of 3 influenza seasons, 146 influenza B viral strains were selected for phenotypic fluorescent assays in order to assess their susceptibility to NI, oseltamivir and zanamivir. For this purpose, was determined the NI concentration required to inhibit 50% of each influenza virus neuraminidase activity (IC50). The IC50 baseline of influenza B viruses was calculated for both oseltamivir and zanamivir using the Robust Excel programme. The neuraminidase gene segments were also monitored for the presence of the main molecular markers, associated with the resistance to neuraminidase inhibitors in influenza B viruses. All analysed influenza B strains proved to be susceptible to oseltamivir and zanamivir. In the 2010/2011 season the determined IC50 values ranged from 0 to 70 nM for oseltamivir and from 0 to 11nM to zanamivir. The zanamivir IC50 median value was about 8-fold lower than oseltamivir IC50 median value. Statistical analysis revealed the presence of one outlier (B/Lisboa/13/2010, 71.08nM) for oseltamivir (2-fold reduction in susceptibility) and four minor outliers (B/Lisboa/15/2010: 9.52 nM; B/Lisboa/19/2010: 9.25 nM; B/Lisboa/51/2010: 10.94 nM and B/Lisboa/53/2010: 9.62 nM) for zanamivir (3-fold reduction in susceptibility) comparing to the median IC50 value. During the 2011/2012 season IC50 values ranged from 23.0 to 38.38 nM (oseltamivir) and from 2.97 to 9.07nM (zanamivir). This season were not found minor or major outliers. The IC50 values obtained in 2012/2013 ranged from 7.91 to 84.84 nM (oseltamivir) and from 1.48 to 5.88 nM (zanamivir). During this last season were found 6 minor and 3 major outliers for oseltamivir and 13 minor outliers for zanamivir. Along the three seasons, the median IC50 values for both NI were higher among the B/Victoria than B/Yamagata viruses. None of the actually known mutations associated with resistance of influenza B viruses to NI was found in the neuraminidase gene (R150K, D197E/N/Y, I221T/V, N294S, R374K and G407S). Influenza B viruses isolated in Portugal during the last three seasons were susceptible to the neuraminidase inhibitors. Portuguese influenza B strains revealed higher susceptibility to zanamivir than to oseltamivir, as observed in other countries. The oseltamivir IC50 values were also different between viruses from the B/Victoria and B/Yamagata lineages, however this was not statistically demonstrated due to the small number of analysed viruses. Among B/Yamagata strains the oseltamivir and zanamivir IC50 values were higher in 2011/2012 than in 2010/2011 and 2012/2013 seasons.